Photoelectron spectroscopy of para-benzoquinone cluster anions - Mensa-Bonsu, Golda; Wilson, Mark R.; Tozer, David J.; Verlet, Jan R.R. (Journal of Chemical Physics, 2019)
The photoelectron spectra of para-benzoquinone radical cluster anions, (pBQ)n− (n = 2–4), taken at hv = 4.00 eV are presented and compared with the photoelectron spectrum of the monomer (n = 1). For all clusters, a direct detachment peak can be identified, and the incremental increase in the vertical detachment energy of ∼0.4 eV n−1 predominantly reflects the increase in cohesion energy as the cluster size increases. For all clusters, excitation also leads to low energy electrons that are produced by thermionic emission from ground electronic state anionic species, indicating that resonances are excited at this photon energy. For n = 3 and 4, photoelectron features at lower binding energy are observed which can be assigned to photodetachment from pBQ− for n = 3 and both pBQ− and (pBQ)2− for n = 4. These observations indicate that the cluster dissociates on the time scale of the laser pulse (∼5 ns). The present results are discussed in the context of related quinone cluster anions.
EPrint Processing Status: Full text deposited in DRO